An Under-the-Table Leg-Movement Apparatus and Changes in Energy Expenditure - Koepp, Gabriel A.; Moore, Graham; Levine, James A. (Frontiers in Physiology, 2017)
Introduction: Deskwork contributes substantially to sedentariness. Here, we evaluated an under-the-table apparatus that was designed to promote leg movement (fidgeting) while seated. Our hypothesis was that the under-the-table apparatus would increase energy expenditure. Methods: We measured energy expenditure and heart rate in 26 people while they sat and worked using a standard chair, walked on a treadmill, and sat and worked using an under-the-desk apparatus that encouraged leg movement. Results: Energy expenditure increased significantly while using the under-the-table apparatus when compared to the standard office chair (standard chair, 81 ± 18 kcal/h; under-the-table apparatus, 96 ± 23 kcal/h) (P < 0.001); representing an 18 ± 16% increase. The changes in energy expenditure were not as great as walking (1 mph, 168 ± 46 kcal/h, P < 0.001; 2 mph, 205 ± 51 kcal/, P < 0.001), representing 107 ± 37% and 155 ± 48% increases over baseline, respectively. Conclusions: An under-the-table apparatus that promotes leg movement can increase energy expenditure by approximately 20%. Dynamic sitting is promoted by this apparatus and may be among a lexicon of options to help people move more while seated at work.